1998
DOI: 10.1029/98je00353
|View full text |Cite
|
Sign up to set email alerts
|

The clouds of Jupiter: Results of the Galileo Jupiter Mission Probe Nephelometer Experiment

Abstract: Abstract. The results of the nephelometer experiment conducted aboard the probe of the Galileo mission to Jupiter are presented. The tenuous clouds and sparse particulate matter in the relatively particle-free 5-/xm "hot spot" region of the probe's descent were documented from about 0.46 bar to about 12 bars. Three regions of apparent coherent structure were noted, in addition to many indications of extremely small particle concentrations along the descent path. From the first valid measurement at about 0.46 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 52 publications
3
55
1
1
Order By: Relevance
“…Particle radii of 0.5-0.75 µm and an optical depth ∼1.6 at λ = 0.5 µm provide a reasonable fit to the observed modulations (Sromovsky et al 1998). It appears that the Nephelometer signals (Ragent et al 1998) may have recorded the very bottom of this upper cloud layer (Fig. 1, right).…”
Section: Probe Observationsmentioning
confidence: 94%
See 2 more Smart Citations
“…Particle radii of 0.5-0.75 µm and an optical depth ∼1.6 at λ = 0.5 µm provide a reasonable fit to the observed modulations (Sromovsky et al 1998). It appears that the Nephelometer signals (Ragent et al 1998) may have recorded the very bottom of this upper cloud layer (Fig. 1, right).…”
Section: Probe Observationsmentioning
confidence: 94%
“…From an analysis of solar modulations in the Net Flux Radiometer (NFR) signals, Sromovsky et al (1998) concluded that there were 1-2 optical depths (at 0.5 µm) of particulates no bigger than about 0.75 µm above the first Probe observation at ∼440 mb. The Nephelometer (Ragent et al 1998) detected very few particulates between 440 mb and 700 mb, where an ammonia cloud had been expected. Both the Nephelometer and the NFR detected a cloud at ∼1.2 bars, with optical depth ranging from τ ∼ 1 at 5 µm (Sromovsky et al 1998) to τ = 1.5-1.8 at 0.904 µm (Ragent et al 1998).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only very thin clouds were found in the Galileo Probe hot spot (Ragent et al 1998), consistent with condensation via weak turbulent updrafts within the descending branch of an equatorially trapped Rossby wave (Friedson 2005;Wong et al 2015). Models of NIMS spectra by Nixon et al (2001) include water clouds in at least some hot spots, and RoosSerote et al (2004) showed that NIMS spectra of hot spots cannot rule out water clouds whose opacity is entirely restricted to P 5 > bar.…”
Section: Introductionmentioning
confidence: 93%
“…Fig. 1 shows results of ECCM calculations for Jupiter, with 1 Â solar and 3 Â solar condensible volatile abundances in the left panel, and greatly depleted condensible volatiles in the right panel (Atreya et al, 1999) as the Galileo Probe entered one of the driest places-the Sahara Desert of Jupiter The right panel simulates the LCL of clouds detected by the Galileo probe nephelometer at 1.3 bar, and more tenuous ones at 1.6 and 0.55 bar (Ragent et al, 1998). Although the H 2 S, and H 2 O mixing ratios in the Probe Entry Site (PES) at pressures less than 9 bar are unknown, their extrapolated values from measured mixing ratios at 9-11 bar (Niemann et al, 1998;Atreya et al, 1999;Atreya et al, 2003), together with the NH 3 profile inferred from the attenuation of Galileo probe radio signal ( Fig.…”
Section: Jupiter's Cloud Modelmentioning
confidence: 99%